2001
DOI: 10.1016/s0002-9440(10)63950-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interferon-γ by Influenza Hemagglutinin-Specific CD8 Effector T Cells Influences the Development of Pulmonary Immunopathology

Abstract: This study examined the inflammation, lung function impairment, and immune protection associated with either wild-type or interferon (IFN)-gamma-deficient Tc1- or Tc2-CD8 effector cells responding to influenza pneumonia. The adoptive transfer of influenza hemagglutinin-specific Tc1 effectors afforded protection and elicited only minimal impairment of lung function. IFN-gamma-deficient Tc1 effector cells were equally protective, but were associated with an eosinophil influx and slightly more lung function impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 17 publications
5
109
2
Order By: Relevance
“…Despite intensive investigation, the degree to which the antiviral and immunopathological effector mechanisms are separable remains unclear. We have previously shown that CD8 þ T-cell recognition of alveolar epithelial antigen results in severe lung inflammation, which is dependent on antigen-specific expression of TNF-a by effector T cells, triggering epithelial cell production of a variety of inflammatory mediators (11,42,45). Excessive chemokine production is known to result in inflammatory infiltration that can lead to tissue injury and organ failure (6,7,41), which we observed in our model.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Despite intensive investigation, the degree to which the antiviral and immunopathological effector mechanisms are separable remains unclear. We have previously shown that CD8 þ T-cell recognition of alveolar epithelial antigen results in severe lung inflammation, which is dependent on antigen-specific expression of TNF-a by effector T cells, triggering epithelial cell production of a variety of inflammatory mediators (11,42,45). Excessive chemokine production is known to result in inflammatory infiltration that can lead to tissue injury and organ failure (6,7,41), which we observed in our model.…”
supporting
confidence: 58%
“…Five days after virus infection, the animals were anesthetized, a tracheostomy tube was inserted, and whole-lung diffusing capacity was determined by CO uptake (a surrogate for oxygen transfer), as previously described (11). In some experiments the partial arterial pressure of oxygen was measured in samples from the ventral tail artery, as previously described (42). Viral titers in whole-lung homogenates were determined as TCID 50 in MDCK cells (43).…”
Section: Methodsmentioning
confidence: 99%
“…This has been demonstrated in the immune response to influenza, where CD8 effectors unable to secrete IFN-γ caused more lung damage than Tc1 effectors capable of producing IFN-γ [53]. Similarly, CD8 cells in chronic LCMV infection were shown to induce wasting disease in IFN-γ-deficient, CD4-depleted mice [21].…”
Section: Cd4 Effector Mechanisms and Protectionmentioning
confidence: 79%
“…This suggests that IFN-γ secretion by CD8 cells exerts a protective effect during immune-mediated damage in the lung and other organs. Indeed, damage mediated by Tc1 IFN-γ −/− and Tc2 IFN-γ −/− effectors included increases in eosinophilia and necrotizing lesions [53]. It is not known to what extent CD4 cells contribute to lung immunopathology after influenza infection, however, it is known that Th2 cells do not protect against lethal influenza infection [51] and the reason for this may be due to increased pathology mediated by the type 2 cytokines, IL-4 and IL-5 leading to eosinophilia.…”
Section: Cd4 Effector Mechanisms and Protectionmentioning
confidence: 99%
“…Consistent with this observation, the frequency of cells presenting MHC class I-and class II-restricted antigenic peptides is indeed highest in the infected lung (S. R. Crowe and D. L. Woodland, unpublished observations) (22,35,36). It is also conceivable that the highly inflammatory environment in the infected lung enhances IFN-␥ expression, potentially synergizing with increased antigenic stimulation (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%